Особливості роботи алгоритмів штучного інтелекту у мобільних застосунках - Вовченко, Т. В. (ХНУРЕ, 2025)
Artificial intelligence is actively used in mobile applications, in particular for image processing. This allows you to perform classification, detection and segmentation of objects. One of the main tools for implementing AI on mobile devices is TensorFlow Lite, which allows you to effectively use model optimization. The paper examines the features of AI algorithms, in particular convolutional neural networks (CNN) and YOLO, their role in mobile applications and the importance of hardware acceleration. Given the leadership of Android in the Ukrainian market, the development of mobile solutions using AI opens up new opportunities for various industries.
Keywords: штучний інтелект; мобільний застосунок